Racial pay parity in the public sector: the overlooked role of employee mobilization - Perera, IM; King, D (SAGE Publications, 2020)
Rising economic inequality has aggravated long-standing labor market disparities, with one exception: government employment. This article considers the puzzle of black-white wage parity in the American public sector. African Americans are more likely to work in the public than in the private sector, and their wages are higher there. The article builds on prior work emphasizing institutional factors conditioning this outcome to argue that employee mobilization can motor it. As public sector unions gained political influence postwar, their large constituencies of black, blue-collar workers, drawing on both militant and nonviolent tactics of the urbanizing civil rights movement, advocated for improved working conditions. Archival sources confirm this pattern at the federal level. The employment and activism of African Americans in low-skilled federal jobs pivoted union attention to blue-collar issues and directly contributed to the enactment of a transparent, universal wage schedule for the blue-collar federal workforce (the Federal Wage System). The result was greater pay parity for African Americans, as well as for other disadvantaged groups.